Evaluation of patient-reported outcome measurements as a reliable tool to measure acceptability of the taste of paediatric medicines in an inpatient paediatric population. Issue 7 (11th July 2018) - Mistry, Punam; Stirling, Heather; Callens, Claire; Hodson, James; Batchelor, Hannah
Abstract : Objective: To evaluate the age appropriateness and suitability of patient-reported outcome measures to assess the acceptability of the taste of oral liquid medicines in children. Design and setting: An observational mixed-methods study involving children aged 2–16 years taking oral liquid medicine in paediatric inpatient wards across the West Midlands (UK). Assessment tools included patient-reported scores on the taste of medicines via a five-point Facial Hedonic Scale; a Visual Analogue Scale (VAS); a question, 'Did you think the medicine tasted OK?' and researcher observations of facial expressions and behaviours immediately before, during and after administration. Results: 611 children participated. The percent unable to complete the scales was 7% (n=46) for the VAS; 2% (n=15) for the hedonic scale and 1% (n=7) for the question about taste. Significant correlations (Spearman's r) were observed between the patient-reported outcome measures: 0.80 and 0.78 for the taste question and hedonic and VAS, respectively, and 0.84 for the hedonic and VAS. Researcher observations demonstrated the ability of the patient to take the medicine as intended but did not provide sensitive measures of taste. 5% of administrations were not taken as intended by the children. Medicines known to have poor taste (clarithromycin and prednisolone) showed mean hedonic and VAS scores of ≥3.5 and >65 mm, respectively. Conclusions: Patient-reported outcome measures correlate with each other and are a useful means to assess the taste (and acceptability) of medicines. Hedonic scales are better understood by children and should be the first choice tool in the assessment of medicines taste.